PERLINDUNGAN HUKUM TERHADAP PEKERJA WANITA YANG BEKERJA PADA MALAM HARI OLEH PENGUSAHA HIBURAN MALAM: Studi Kasus Tempat Karaoke di Kota Surabaya - Zalzabillah Nanda Fatrisa (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
In this study, the author aims to find legal clarity regarding legal protection for female workers who work at night in nightclubs. This study uses empirical research methods, namely research conducted by going directly to the research location and conducting observations, documentation and interviews. This research was conducted by analyzing the legal principles, theories and concepts as well as the statutory provisions related to case studies regarding the consequences of women working at night. The problem in this study is that there are still many women who work at night who have not received guaranteed protection from the workplace. The researcher uses a concept that has been designed in such a way as to find legal clarity regarding legal protection for women who work at night, in which case the rights of these women workers have not been fulfilled and the obligations of the entrepreneur are not carried out properly and correctly